DAYA TETAS TELUR IKAN PATIN (Pangasius hypophthalmus) PADA pH MEDIA BERBEDA - Prily Lovian Putra; Dade Jubaedah; Mochamad Syaifudin (Jurnal Akuakultur Rawa Indonesia, 2020)
The pH of waters is one of external factors that is important for succesfull of hatching percentage of fish eggs. The pH stimulates the chorionase enzyme become more active that can softens the egg chorion. The aim of this study was to determine the optimum pH value for hatching of catfish eggs. This research has been conducted in Fisheries Basic Laboratory, Department of Aquaculture, Department of Fisheries, Agriculture Faculty, Universitas Sriwijaya from August 31st to September 16th, 2019. The research metehod used Completely Randomized Design with five treatments and 3 replications. The treatments are P1 (pH of 5±0.2), P2 (pH of 6±0.2), P3 (pH of 7±0.2), P4 (pH of 8±0.2) dan P5 (pH of 9±0.2). The results showed that different value of water pH gave significant effect on hatching percentage, hatching time and survival rate of catfish larvae but did not significant effect on percentage of abnormal larva. The highest hatching percentage (80.33 %) was in treatment of pH 7 ± 0.2 (P3), the fastest hatching percentage (21.59 hours) was in treatment of pH 8 ± 0.2 (P4), the highest survival rate of catfish larvae (99.44 %)  was in treatment of pH 7 ± 0.2 (P3) and the highest percentage of abnormal larvae (2.22 %) was in treatment pH 5 ± 0.2 (P1). During the research, water quality were in tolerance range for hatching and rearing of eggs and larvae catfish i.e. temperature of 26.2 – 27.9 oC, dissolved oxygen of 4.7 – 5.5 mg.l-1, and ammonia of 0.22 – 0.47 mg.l-1.Keyword : Hatching eggs, catfish, pH value